2018
DOI: 10.1007/s00394-018-1687-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between fruit and vegetable intake and the risk of hypertension among Chinese adults: a longitudinal study

Abstract: Greater long-term intake and increased intake of fruit and vegetables may reduce the risk of developing hypertension in Chinese adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
2
20
1
Order By: Relevance
“…Other studies conducted among 28,082 female health professionals in the United States and a prospective cohort study among 745 residents aged 35 years without home hypertension at baseline from Ohasama, Japan, also reported a relationship between fruit consumption and decreased risk of hypertension [37, 38]. Lately, a longitudinal study conducted in China affirms that fruit intake was more robustly and significantly associated with lowering blood pressure than vegetable intake [39]. However, Nunez-Cordoba et al reported no association between fruit intake and risk of hypertension [40], which needs to be researched further.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies conducted among 28,082 female health professionals in the United States and a prospective cohort study among 745 residents aged 35 years without home hypertension at baseline from Ohasama, Japan, also reported a relationship between fruit consumption and decreased risk of hypertension [37, 38]. Lately, a longitudinal study conducted in China affirms that fruit intake was more robustly and significantly associated with lowering blood pressure than vegetable intake [39]. However, Nunez-Cordoba et al reported no association between fruit intake and risk of hypertension [40], which needs to be researched further.…”
Section: Discussionmentioning
confidence: 99%
“…43) Some studies have reported that the inverse relationships between fruit and blood glucose or blood pressure were attenuated or made non-significant when the models were adjusted for adiposity. 37,38) However, most studies have reported that adjustment of the adiposity index did not significantly change the association between fruit intake and blood glucose level 19) or blood pressure. 35,36) This suggests that fruits have other positive properties, such as anti-oxidative and anti-inflammatory effects, and ability to improve endothelial function and glucose metabolism, besides their anti-obesity effects.…”
Section: Implications When Analyzing Fruit Intake and Health-related Studiesmentioning
confidence: 98%
“…36) The China Health and Nutrition Survey showed a similar protective effect, in that each standard deviation increase in fruit intake during the 5-year follow-up was associated with a 0.273 (0.058 to 0.487; P=0.013) mm Hg decrease in diastolic blood pressure, and a 0.264 (-0.578 to 0.049; P=0.098) mm Hg decrease in systolic blood pressure. 37) In summary, a fruit intake of up to 530-600 g/d is protective against incident hypertension.…”
Section: Hypertension 1 Does Fruit Intake Prevent Hypertension?mentioning
confidence: 99%
“…Participants under the age of 18 (n = 4408) and those who died before 2004 (n = 50) were excluded. Due to unreliable dietary intake data, subjects with excessively low or high energy intake (<500 kcal/day or >4000 kcal/day, n = 105) were excluded [14,15]. Furthermore, subjects with stroke, cancer, or myocardial infarction at baseline (n = 365) were excluded.…”
Section: Study Design and Participantsmentioning
confidence: 99%